ANALYSIS AFTER SALES SERVICE IN EFFORT TO IMPROVE COSTOMER SATICFACTOIN ON PT. NUSANTARA MOTOR IN BALIKPAPAN - -, Mursidah - (EKONOMIA, 2014)
Research purpose  is to determine  the effect after sales service  to the costomer saticfaction  on PT.Nusantara Motor.while the usefulness of this study  infut material for the company in planning and improve marketing strategy in particular after sales service accordance with the needs and costumer desires. Analysis tolls used is simple linier regression equation Y= a+bx. Scale coefficient regression (b) =0,9874 , this means there is an increase costumer  saticfaction  in influenced by  the lever that after sales service , so that the costumer saticfaction and increased  by 0,9874  white  the constant value (a) = 0,0478 this can aftect a change costumer  saticfaction  and service improvement after sales applied by the company.thus chan  be a portraid  of value of the regression equation, Y= -0,0478 + 0,9874x the calculation value of correlation coeffient  (r) =0,9076 means shows that there is the closeness of the relationship between variables after sales servis to the variable costumer satisfaltion and can be expressed a significant relationship and fositif on the correlation coefficient. Value coefficient determination or coefficient determinan ( kp ) =0,8238 this means an increase costumer satisfaction influenced by the sales service. And if persentase after sales service ( variable ) contribute to the custumer r (variable Y)  of 82,38% and the rest of 0,1762 or 17,62% this is aftected or contributed by the variable that can not be described in this study. The calculation test hypothesis test the appointment of that the value t count greater than t table or sign up a namely t 16,4667 and t table 2,000, thus the hypothesis provious acceptable.